Comment on “The effect of hyperbaric oxygen therapy on rectal ulcers after Argon plasma coagulation” - Cunha Neves, João A. (2021)
Dear Editor, We read with great interest the paper by Laranjo et al. [1] entitled “The Effect of Hyperbaric Oxygen Therapy on Rectal Ulcers after Argon Plasma Coagulation.” The authors reported the case of a patient with chronic radiation proctitis, who developed rectal ulcers after endoscopic treatment with argon plasma coagulation (APC) and was successfully treated with hyperbaric oxygen therapy (HBO). Although it is well established that HBO therapy is an effective alternative treatment for patients with radiation-induced rectal ulcers and severe chronic proctitis [2, 3], its application has not been described as a treatment option in APC-induced rectal ulcers. We acknowledge the authors’ awareness of HBO as an option for complications induced by conventional chronic proctitis treatments and we would like to share our experience on this particular matter. A 72-year-old female patient was admitted to our Emergency Department with rectal bleeding, acute anal pain, and iron deficiency anemia (hemoglobin 10.7 g/dL). She had a past medical history of endometrial carcinoma treated with radio- and brachytherapy 2 years before. Total colonoscopy revealed multiple bleeding rectal radiation-induced telangiectasias. Medical treatment with topical salicylates and sucralfate for 8 months was unsuccessful and APC therapy (45 W; 1.5 L/min gas flow) every 4 weeks was initiated. The patient was submitted to a total of 6 APC sessions, with an overall endoscopic improvement between the first and third sessions. However, amidst the fourth and sixth APC sessions, the patient developed multiple APC-induced ulcers and an ulcerated stenosis of the distal rectum.